Makna Kalalah dan Penindasan Hak Perempuan - Muhammad Rikza Muqtada (UIN Sunan Kalijaga Yogyakarta, 2015)
The article discusses the shifting process of free inheritance system (wasiat) into the codified one (ilm al-faraidh). In this shift of system, Hadis serves as its key factor. In the realm of interpretation discourse and Islamic Law, al-Syafi’i pays keen attention on the use of Hadis. In addition, the use of Hadis implicates a sequence of methodologies in order to support certain arguments, such as found in the ijma’.The use of hadis relatively functions as mediation of various ideas, applying particular way toward certain intended conclusion. Having utilized the methodological formulation, Al-Syafi’i, in this regard, situates the involvement in the interpretation of inheritance verses (QS. 4:11-12 and 176). Al-Syafi’i’s view has deeply embedded in al-Thabari, one of the interpreters on the school. Both al-Syafi’i and al-Thabari have implemented Hadis as the main source in interpretating of the inheritance verses. As the result, it reveals the following concluding remarks: 1). the deletion of the wasiat verses with the inheritance ones, 2). the codification of reading in a passive form (yuratsu and yusa), and 3). the codification of “kalalah” meaning becoming all the heirs except mother, father and the children. Although the codification can mediate the debates, it still reveals a further complicated problem.The problem is on the fact that there are some heiress that actually deserved on the inheritance, but they are in the danger of disinheritance. In inheritance context, it serves not only the passing process of the property between previous and recent generations, but it also relates women’s existence and the positionality vis a vis that of men. In a historical investigation and cross-reference, it is profound that the meaning of “kalalah” denoted female in law (wife, daughter in law or probably sister in law) that deserved as the heiress of the man.[Tulisan ini menggambarkan proses perubahan sistem waris yang bebas (wasiat) menjadi sistem waris yang baku (ilm al-faraid). Dalam perubahan ini, hadis memegang peran kunci. Dalam percaturan wacana penafsiran maupun hukum Islam, penggunaan hadis telah ditanamkan sebegitu penting oleh al-Syafi’i. Melalui hadis juga terbentuk seperangkat metodologi, seperti ijma’, yang bisa dijadikan sebagai penguat sebuah argumentasi. Penggunaan hadis pun mampu menutup segala bentuk perbedaan pendapat, dengan menggiringnya pada satu kesimpulan yang dikehendaki. Dengan rumusan metodis yang ditanamkan, al-Syafi’i otomatis terlibat dalam percaturan wacana penafsiran ayat waris (QS. 4:11-12 dan 176). Pandangan al-Syafi’i mampu mengakar kuat dalam benak para penafsir di kalangan mazhabnya, di antaranya al-Thabari. Baik al-Syafi’i maupun al-Thabari, hadis dijadikan rujukan utama dalam penafsiran ayat waris ini, sehingga menghasilkan kesimpulan bertahap: 1) adanya pembatalan ayat wasiat oleh ayat waris, 2) pembakuan bacaan dalam bentuk pasif (yuratsu dan yusa), dan berakhir pada 3) pembakuan makna kalalah menjadi semua ahli waris selain ibu-bapak dan anak. Meskipun pembakuan ini mampu meredam perdebatan, tetapi tetap meninggalkan problematika yang lebih rumit. Ada beberapa golongan perempuan yang sebenarnya berhak menerima warisan, kini terhapuskan dari daftar ahli waris. Dalam pewarisan bukan semata pengaturan peralihan kekayaan antar generasi, tetapi juga menyangkut kedudukan dan eksistensi perempuan vis a vis dengan laki-laki. Melalui investigasi historis dan cross refrence, terungkaplah makna kalalah sebagai female in law (istri, menantu perempuan, atau mungkin ipar perempuan) yang berhak menerima warisan almarhum.]